Cycloparaphenylene-Derived Porous Organic Cylinders - Zi-Ye Huo; Liang-Liang Mao; Lixia Guo; Lu Li; Xueliang Shi; Gaolei Li; Jia-Nan Gao; Hai-Bo Yang; Wen Zhou; Hongwei Li; Shengchang Xiang; Sihai Yang; et al. (Journal of the American Chemical Society, 2026)
Abstract Cycloparaphenylenes, with their distinctive radial conjugation and high macrocyclic rigidity, hold significant yet underexplored potential for the development of novel porous structures. We report the rational design and facile synthesis of three porous organic cylinders (POCys). Through dynamic boronate ester linkages, the coaxial covalent assembly of two catechol-functionalized cycloparaphenylenes could generate cylindrical scaffolds featuring large intrinsic cavities with interconnected channel networks. One of the POCys exhibits high porosity, showing a Brunauer–Emmett–Teller surface area of 1241 m2·g–1 and excellent gas adsorption capability. This work demonstrates the promise of cycloparaphenylene derivatives as a molecular platform for designing functional porous organic architectures.